Gerakan Ekofeminisme Perempuan Adat Mollo dalam Menolak Tambang Marmer: Studi: Penolakan Tambang Marmer Di Desa Fatumnasi, Kabupaten Timor Tengah Selatan - Ita Irianti Selan; Esrah D.N.A Benu; Diana S.A.N Tabun; Rudi Rohi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study is entitled “The Ecofeminist Movement of Mollo Indigenous Women in Rejecting Marble Mining (study: Rejection of Marble Mining in Fatumnasi Village, South Central Timor Regency)” which aims to understand and analyze the ecofeminist movement carried out by Mollo indigenous women in rejecting marble mining activities in Fatumnasi Village. The presence of marble mining in the Mollo indigenous area has posed a threat to Environmental sustainability, water sources, and cultural values that have long been the identity of the community. Through a descriptive qualitative approach, this study describes the role and form of resistance of Mollo indigenous women based on the ecological relationship between women and nature. Data were obtained through in-diepah interviews, field observations, and documentation of the head of Fatumnasi Village, traditional women’s figures, religious figures, community leaders, and youth leaders. The results of the study indicate that the movement to reject marble mining is not merely a form of protest against environmental damage, but also a form of ecofeminist awareness that emphasizes that women’s bodies and the body of nature are an inseparable whole. This movement is expressed through various acts of resistance such as traditional rituals, weaving, demonstrations, and customary deliberations, each carrying symbolic meaning about the harmony between humans and nature. Based on Françoise d’Eaubonne’s theory of ecofeminism, the Mollo women’s movement reflects critical awareness toward patriarchal and capitalist systems that exploit both women and the environment. Thus, it can be concluded that the ecofeminist movement of Mollo indigenous women in rejecting marble mining is a form of women’s struggle to maintain environmental sustainability and maintain cultural identity through loclah wisdom practices.Ecofeminism, Mollo Indigenous Women, Marble Mining, Fatumnasi Village, Environment